Histopathological Study of Gallbladder Associated with Gallstone Disease - Seerwan Raheem; Ismail Kakey (Kirkuk Journal of Science)
Gallstones are a medical condition that is found all over the world. However, the rates of occurrence vary significantly depending on the geographical location. The present study aims to examine the histopathological changes in the mucosa of the gall bladder in patients with cholelithiasis. The study involved 81 patients who were treated with a gallbladder removal operation due to cholecystitis. The patients were divided into groups according to their symptoms. The histological study involved fixing gallbladder samples in 10% formalin, dehydrating them in ethanol, clearing them in xylol, and embedding them with paraffin wax. Sections were cut, stained, and viewed under a light microscope. The result of this study reveals variations in gallstone disease distribution concerning symptoms. patients without symptoms represent (23.45%), Patients with mild symptoms and without complications represent (35.80%), patients with severe symptoms without complications represent (12.35%), and patients with severe symptoms and complications represent (28.40%). The following abnormalities in gallbladder tissue are presented: Some pouching of mucosal epithelium was found, which extended from the surface epithelium into the deep muscle layer of the gallbladder. Disruption of the epithelium, irregular surfaces, and vacuolated cytoplasm were found in the gallbladder epithelium. The tissue section showed infiltration of some inflammatory cells, lymphocytes, and plasma cells, and some types of macrophages of the gallbladder mucosa with chronic inflammatory cells associated with epithelial hyperplasia, bleeding in blood vessels was frequently occurring. The study concluded that pathological alterations in the gallbladder epithelium may contribute to gallstone development.